2018
DOI: 10.1002/advs.201800852
|View full text |Cite
|
Sign up to set email alerts
|

Development of Biocompatible HA Hydrogels Embedded with a New Synthetic Peptide Promoting Cellular Migration for Advanced Wound Care Management

Abstract: In the past few years, there have been many efforts underway to develop effective wound healing treatments for traumatic injuries. In particular, wound‐healing peptides (WHPs) and peptide‐grafted dressings hold great promise for novel therapeutic strategies for wound management. This study reports a topical formulation of a new synthetic WHP (REGRT, REG) embedded in a hyaluronic acid (HA)‐based hydrogel dressing for the enhancement of acute excisional wound repair. The copper‐free click chemistry is utilized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…On the other hand, the strength of the repaired tissue mainly depends on the orientation of the regenerated collagen. Therefore, a large number of reports suggest that more collagen deposition , during the proliferative phase, and a more consistent collagen trend in the remodeling phase indicates better wound healing efficiency.…”
Section: The Process Of Skin Repair and Evaluation Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the strength of the repaired tissue mainly depends on the orientation of the regenerated collagen. Therefore, a large number of reports suggest that more collagen deposition , during the proliferative phase, and a more consistent collagen trend in the remodeling phase indicates better wound healing efficiency.…”
Section: The Process Of Skin Repair and Evaluation Parametersmentioning
confidence: 99%
“…The larger material-tissue contact area makes it possible to obtain cells, tissues, RNA, exudate, and tissue specimens from larger cross-sectional area and volume, which is more conducive to the detection of some further biochemical and histological parameters. Specifically, various parameters such as wound closure rate, inflammation cell (not caused by bacteria), granulation tissue formation, re-epithelialization, collagen deposition, angiogenesis, hair follicle formation, and a series of healing-related cells ,,, and cytokines were used to evaluate the healing process of excisional wounds. Figure B shows an example of the preparation of nanocomposite adhesive conductive self-healing antibacterial anti-oxidation multifunctional hydrogel based on the enzyme-catalyzed polymerization of dopamine between hyaluronic acid grafted dopamine and GO coated dopamine.…”
Section: Type Of Wound Applied With Hydrogel Dressingmentioning
confidence: 99%
“…Histological examination showed that the HA dressing accelerates re-epithelization in skin wound healing, particularly by promoting migration of fibroblasts, keratinocytes and endothelial cells. The peptide-grafted HA hydrogel system can be considered as state of the art technology for wound repair [92] .…”
Section: Biomaterials For Wound Managementmentioning
confidence: 99%
“…VEGF activates the ERK and Akt signalling pathways, leading to metalloproteinase secretion, which degrades the basement membrane. This activation and subsequent degradation are followed by cytoskeletal remodelling with F-actin polymerization and filopodia extension, allowing endothelial cells to migrate into the wound area [118].…”
Section: Regulating Cytoskeleton Rearrangementmentioning
confidence: 99%